(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Alien species are reaching different areas, including also cemeteries. Inventory of invasive flora of cemeteries of the city of Daugavpils actually is the first such type of work to such level of detail on the Latvian scale. Field studies were conducted in 10 cemeteries of the city of Daugavpils. The obtained results are indicative of a comparatively high proportion of invasive plant species in the cemeteries. 49 invasive alien species were found. In the cemetery areas these are spreading mainly from greeneries, but there are also such taxa, which have accidentally reached the cemeteries. The most frequent plant in the Daugavpils cemeteries is Spiraea chamaedryfolia. Taking into account the trends of migration, sex-age structure of population, climate change, availability of exotic and new ornamental plants, it is most likely that the number of invasive species will grow in the future.